The Contribution of ICT in Agricultural Development In Kostratani of BPP Bojonggambir, Tasikmalaya - Bambang Ngaji Utomo; NLP. Indhi Dharmayanti; Tatan Sukmayandi; Ermin Widjaja (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2022)
This study was to see the role of ICT in BPP Kostratani Bojonggambir in supporting the extension program. This research was carried out in the working area of BPP Bojonggambir, in the form of qualitative descriptive research with primary and secondary data collection. The data and information were analyzed descriptively in the form of tables and graphic and SWOT analysis. The location of the villages that are far from each other is thought to affect the dissemination of agricultural technology, as it can be seen from the application of technology at main commodities which is still < 70%, except for chili commodities which > 70% because their activities are commercially oriented. BPP counseling activities are still dominated by face-to-face and field visits, while the use of ICT was to help the implementation of tasks at BPP (60%) and improve the quality of BPP human resources (63.7%), while related to extension activities to the farmers or group of farmers was only 18.2%. The strategies in the use of ICT in the farmers or farmer group based on a SWOT analysis require commitment from various parties, especially ICT pioneers in term of Agricultural Operasional Room and their infrastructure in the group of farmers and also improving the quality of IT of human resources both at BPP and group of farmers.